Identification of Accounting Errors and Fraud: Case Study - Raziūnienė, Daiva; Juškaitė, Gintarė (Buhalterinės apskaitos teorija ir praktika, 2020)
Fraud from errors can only be distinguished by using the rejection method, when the found inaccuracy is checked using methodology for fraud detection. Therefore, the three most popular methodologies are examined: the fraud triangle, ratio analysis, and forensic accounting. The fraud triangle and the ratio analysis makes it easier to identify fraud than forensic accounting, but these methods require additional evidence to confirm the fraud. Forensic accounting uses document verification, so this method does not require additional evidence, whereas the forensic expert decides within his competence on error and fraud. The purpose of the article is to conduct a case study, which aims to determine the progress of investigating errors and fraud and the applicable illegal actions after examining a case of document forgery. In the case analysis fraud was found in the company's accounting by using document verification and comparison as well as interviewing employees. The following research methods were used for the research: comparative analysis and synthesis of scientific literature, interpretation, deduction, systematization, generalization, case analysis.
Keywords: error; fraud; accounting; forensic accounting